Developing Business Strategy To Achieve Sustainable Gas Deliverability Business For Kangean Energy Indonesia Ltd. Through Scenario Planning - Samara Natalia Siregar, Raissa; Sunitiyoso, Yos (GEMA EKONOMI, 2023)
Indonesia's rapid economic growth has increased energy demands, necessitating a robust energy security strategy. In this context, natural gas is crucial as a transitional energy source for achieving net-zero emissions. Despite the abundance of natural gas reserves in the country, the government foresees a potential imbalance between demand and supply, posing risks of disruptions in the energy sector. To address these challenges, this study focuses on formulating a business strategy for Kangean Energy Indonesia Ltd. (KEI) over the next five years, focusing on ensuring sustainable gas deliverability through applying qualitative scenario planning. Scenario planning is a valuable analytical tool to identify and address the uncertainties that may impact the Indonesian gas industry. This methodological approach builds a strong foundation for developing effective business strategies. Â The research draws upon both primary and secondary data sources. Based on a comprehensive stakeholder mapping, primary data is acquired through interviews with eight carefully selected stakeholders. Through these interviews, the study highlights two critical uncertainties that significantly influence the gas industry: supply and infrastructure. The study culminates in creating a comprehensive scenario framework complemented by detailed narratives exploring plausible future developments. Furthermore, the research delves into the implications and options for alternative strategies in light of these scenarios. Additionally, identifying early warning signals becomes instrumental in KEI's agile response to potential changes in the industry landscape. Through this approach, KEI can enhance its preparedness to address future challenges, ensuring sustained success in the dynamic and ever-evolving gas deliverability business. As Indonesia's energy landscape continues to evolve, KEI's commitment to scenario planning will be instrumental in securing the nation's stable and prosperous energy future